Are We Richer than Our Parents Were? Absolute Income Mobility in Australia. Issue 320 (29th October 2021) - Kennedy, Tomas; Siminski, Peter
Abstract : We conduct the first dedicated study of absolute income mobility in Australia for the period 1950–2019. Approximately two‐thirds of 30–34‐year‐olds have higher real incomes than their parents did at the same age, and this has been stable for 25 years. This is a high level of mobility among countries where estimates are available. Nevertheless, mobility has declined. Over 80 per cent of baby boomers had higher incomes than their parents. Some two‐thirds of this decline is due to lower income growth. The remainder is due to rising inequality. The mobility estimate is higher (78 per cent) when income is adjusted (equivalised) for family size.